Pío del Río-Hortega: A Visionary in the Pathology of Central Nervous System Tumors - Ramon y Cajal Agüeras, Santiago (Frontiers in Neuroanatomy, 2016)
The last 140 years have seen considerable advances in knowledge of central nervous system tumors. However, the main tumor types had already been described during the early years of the twentieth century. The studies of Dr. Pío del Río Hortega have been ones of the most exhaustive histology and cytology–based studies of nervous system tumors. Río Hortega’s work was performed using silver staining methods, which require a high level of practical skill and were therefore difficult to standardize. His technical aptitude and interest in nervous system tumors played a key role in the establishment of his classification, which was based on cell lineage and embryonic development. Río Hortega’s approach was controversial when he proposed it. Current classifications are based not only on cell type and embryonic lineage, as well as on clinical characteristics, anatomical site, and age.